1995
DOI: 10.1128/aac.39.5.1182
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of pefloxacin in feces during infection prophylaxis in neutropenic patients

Abstract: Pefloxacin (400 mg twice daily) was administered orally for infection prophylaxis in neutropenic patients. Diffusible fecal pefloxacin concentration was determined by bioassay during 24 neutropenic periods. The median diffusible fecal pefloxacin concentration was 187 g/g. This concentration was comparable with those found in volunteers following oral and intravenous administration of pefloxacin (400 mg twice daily) (median of 171 and 155 g/g, respectively). From this study, it is concluded that pefloxacin admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…Our results differ from those of previous studies, which found that fluoroquinolone prophylaxis leads to marked reduction and often complete elimination of members of the family Enterobacteriaceae from fecal flora, with little or no emergence of fluoroquinolone resistance (3,11,22,25). This difference may be explained in part by the fact that our study was conducted in a community in which the incidence of quinolone use is high and the prevalence of quinolone resistance appears to be increasing (21).…”
contrasting
confidence: 99%
“…Our results differ from those of previous studies, which found that fluoroquinolone prophylaxis leads to marked reduction and often complete elimination of members of the family Enterobacteriaceae from fecal flora, with little or no emergence of fluoroquinolone resistance (3,11,22,25). This difference may be explained in part by the fact that our study was conducted in a community in which the incidence of quinolone use is high and the prevalence of quinolone resistance appears to be increasing (21).…”
contrasting
confidence: 99%
“…The comparison is between three options:no antibiotic prophylactic regimens, vancomycin or ciprofloxacin and amoxicillin-clavulonic acid. However, it is not randomised Reuter 2005 Not an RCT, a prospective observational study Risi 1998 A review article Schaison 1991 A study of febrile neutropenia Solano 2005 Not a randomised trial - a prospective study of prophylaxis compared with historical controls Spanik 1998 A retrospective trial Takemoto 1990 A randomised controlled trial but for febrile neutropenia Timmer-Bonte 2005 A randomised controlled trial, but the intervention was granulocyte colony-stimulating factor and both arms received prophylactic antibiotics Tjan Heijnen 2002 A letter relating to another trial Tunkel 2002 A review article Van De Leur 1995 A study which evaluates antibiotic concentration in faeces, but not in neutropenics, not a RCT Viscoli 2001 A review article Viscoli 1998 A review article Viscoli 2002 A review article von Baum 2006 Controlled before and after observational study of prophylaxis but not randomised von Minckwitz 2008 This study compared four consecutive cohort studies of patients receiving chemotherapy for breast cancer, it was not randomised. The 4 methods of neutropenia prophylaxis administered were : ciprofloxacin alone vs figrastim vs. pegfilgratim vs pegfilgradtim+ciprofloxacin Wade 1981 A retrospective study…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Likewise, pefloxacin is more lipophilic than ciprofloxacin and fleroxacin which further contributes to the complete bioavailability of pefloxacin. A major part of pefloxacin is recovered in feces [16] and pefloxacin reaches high concentrations in this matrix [64,65]. While these data show that pefloxacin is present at considerable concentrations in the gut and ultimately in feces, they also suggest that reabsorption of pefloxacin is less than 100%.…”
Section: Discussionmentioning
confidence: 99%